2013
DOI: 10.3354/ab00496
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory electron transport system activity in symbiotic corals and its link to calcification

Abstract: Scleractinian corals host photosynthetic endosymbionts, making direct measurement of the host respiration rate via incubation methods based on O 2 consumption impossible. We tested the use of the respiratory electron transport system activity (ETSA) for measuring host potential respiration. The applied method, modified from a previous study, is based on the reduction of (4-iodophenyl)-3-(4-nitrophenyl)-5-phenyl-2H-tetrazolium chloride (INT) to formazan. After the development of a protocol suitable for corals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Values of respiratory ETSA suggested that potential respiration of host coral decreases under cold stress. We performed all ETSA measurements at 25 °C to compare the state of the enzymatic system under analogous conditions; the actual ETSA at 13 °C would have been even lower, due to its positive correlation with temperature 27 . The decrease in potential respiration rates, as measured by ETSA, and in actual respiration rates could be due to a continuous decrease in the amount of substrate available for respiration, potentially contributing to the decreased calcification rates by limiting the energy available for the calcification process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of respiratory ETSA suggested that potential respiration of host coral decreases under cold stress. We performed all ETSA measurements at 25 °C to compare the state of the enzymatic system under analogous conditions; the actual ETSA at 13 °C would have been even lower, due to its positive correlation with temperature 27 . The decrease in potential respiration rates, as measured by ETSA, and in actual respiration rates could be due to a continuous decrease in the amount of substrate available for respiration, potentially contributing to the decreased calcification rates by limiting the energy available for the calcification process.…”
Section: Discussionmentioning
confidence: 99%
“…After sonication, the suspension was centrifuged at 14,000 × g for 10 min and used as the zooxanthella fraction for protein and enzyme assays. The ETSA assay 27 of host extract was conducted after 5 min of sonication (VP-050, TAITEC) at 25% power on ice. The SOD activities of host and zoox fractions were assayed spectrophotometrically 36 37 .…”
Section: Methodsmentioning
confidence: 99%
“…These changes could reflect the availability of translocated carbon-rich material from the symbionts, as nutritional input directly affects respiration (Båmstedt, 1980;Clarke and Walsh, 1993;Holcomb et al, 2014). Indeed, host CS and CCO activities in the reef coral Stylophora pistillata decreased with reduced irradiance (Gattuso et al, 1993), and Symbiodinium density and host mitochondrial electron transport rates or CS activities were positively correlated in six coral species (Agostini et al, 2013) and E. pallida (Hawkins et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Even greater enhancements have been reported for short-term respiration measurements made immediately after light incubations (Edmunds and Davies 1988;Colombo-Pallotta et al, 2010). However, much of this enhancement of respiration may be due to respiration by the zooxanthellae, with a relatively small enhancement in the animal host (Agostini et al, 2013).…”
Section: Respirationmentioning
confidence: 91%